2003
DOI: 10.1111/j.1365-2621.2003.tb09624.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Protein Fractions Isolated from Porcine Blood

Abstract: Red cell concentrate, serum, albumin, and immunoglobulin fractions were separated from porcine blood collected at a HACCP-implemented (Hazard Analysis and Critical Control Points system-implemented) slaughterhouse in Hermosillo, México. Functional and microbiological properties were examined. Red cell concentrate and serum isolates were high in protein (92 and 85%, respectively) but limited in methionine and isoleucine. Porcine serum and albumin fractions showed emulsifying properties comparable to bovine sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Solubility reached near 100% at pH 5.0 and 6.0 and 95% at pH 3.0 and 7.0. Ramos-Clamont et al (2003) also found that the solubility of serum albumin from swine blood was little affected by pH reaching the maximum solubility of 90%. The difference in the maximum solubility of serum albumin from bovine and swine must be attributed to the different amino acid composition in the two species.…”
Section: Jiang He and Fountoulakismentioning
confidence: 91%
“…Solubility reached near 100% at pH 5.0 and 6.0 and 95% at pH 3.0 and 7.0. Ramos-Clamont et al (2003) also found that the solubility of serum albumin from swine blood was little affected by pH reaching the maximum solubility of 90%. The difference in the maximum solubility of serum albumin from bovine and swine must be attributed to the different amino acid composition in the two species.…”
Section: Jiang He and Fountoulakismentioning
confidence: 91%
“…Methods for hygienic collection of animal blood have been developed (Ockerman and Hansen, 2000;Gorbatov, 1988), along with high quality standards for slaughterhouses (Mackey and Roberts, 1993) to obtain edible blood proteins (Ramos-Clamont et al, 2003). The value of animal blood has long been appreciated in Europe and Australia (Pearson and Dutson, 1997), and bovine blood is collected and used to produce a variety of dishes like puddings, pancakes, blood sausage and soups (Ockerman and Hansen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Protein fractionation of porcine serum or plasma may improve the commercial and functional value of blood. Porcine immunoglobulins can easily be incorporated into liquid preparations for veterinary prophylactic purposes, while porcine serum albumin (PSA) can be use as emulsifier (Ramos-Clamont et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In China, about 1,500,000 tons of porcine blood is produced every year (1). It is known that blood is rich in heme iron (2), proteins (3), and other high nutritional and functional ingredients (4). More than 70% protein and nearly total iron in blood are distributed in red blood cell (RBC) (5).…”
Section: Introductionmentioning
confidence: 99%